The theory of «nasikh» in the writings of Husamuddin al-Siganak (Journal of Philosophy Culture and Political Science, 2018)
Everyone is familiar with the fact that for a society in which a particular religion only began to emerge and forthe society in which religious views reached its heights, presentation to the path of religion and ways to strengthenSharia law will not be the same. Excellent wisdom and absolute knowledge of the Creator encompassing allthings, in cases of necessity some sharia rules might be changed from previous sharia norms to benefi t mankind.This phenomenon is known in the Shari’ah on the terms «Nasikh» and «mansukh». This article discusses thetheory of «Nasikh» in the writings of the famous medieval theologian , a lawyer and linguist of Kazakh steppesHusamuddin al-Siganak and issues of Nasikh legal norms in religious texts on the transformation of society andtime.Key words: Husamuddin as-Sygnaki, islam, nasikh, mansukh, law, religious text.